2019
DOI: 10.2478/jee-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Erasure decoding of five times extended Reed-Solomon codes

Abstract: Recently a new family of error control codes was proposed which are equivalent to five times extended Reed-Solomon codes. In this paper an erasure decoding algorithm for these codes is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…• more than two errors in information symbol: In this case the complexity of procedures quantified by Υ 1I , Υ 2I , Υ 1P 1I can be added as the worst case: (16,6,23,9,2). (106)…”
Section: Complexity Estimation Of the Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…• more than two errors in information symbol: In this case the complexity of procedures quantified by Υ 1I , Υ 2I , Υ 1P 1I can be added as the worst case: (16,6,23,9,2). (106)…”
Section: Complexity Estimation Of the Algorithmmentioning
confidence: 99%
“…In [1] it was shown that RS codes could be extended not only three times, but even five times when they are constructed over certain finite fields. For such five times extended RS codes a decoding algorithm is known [2] which is suitable only for erasure decoding. In case of erasures the positions are known in a received vector and therefore only the erasure values have to be found out during decoding.…”
Section: Introductionmentioning
confidence: 99%